Zona Industri Lhok Seumawe (ZILS) Studi Tentang Kesenjangan Sosial Budaya di Aceh Utara - Abdul Rachman Patji (Jurnal Masyarakat dan Budaya, 1998)
This article examines the problems of inequality in the process of social and cultural changes as consequence of big industries development in Aceh Utara, especially at the region called ZILS (Industrial Zone of Lhok Seumawe). The development itself is recognized to be a successful effort to lift up economy condition of the region. However, it also becomes a drive force for the birth of inequality phenomena among groups of society (i.e. industry, in-migrant and local people) in this region. Some important aspects of the inequality are caused by the imbalance patterns in fulfilment necessity of the groups, the inappropriateness of social and cultural considerations at industry planning and, last but not least, lack of harmonious communication between the people of industry, regional government and local society.